Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Solve for [tex]\( x \)[/tex]:
[tex]\[ 3x = 6x - 2 \][/tex]


---

The vertex form of the equation of a parabola is [tex]\( y = (x + 5)^2 + 49 \)[/tex]. What is the standard form of the equation?

A. [tex]\( y = x^2 + 49x + 35 \)[/tex]
B. [tex]\( y = 5x^2 + 10x + 74 \)[/tex]
C. [tex]\( y = x^2 + 10x + 74 \)[/tex]
D. [tex]\( y = x^2 + 5x + 49 \)[/tex]


Sagot :

To convert the equation of a parabola from vertex form to standard form, we need to expand and simplify the expression.

Given vertex form:
[tex]\[ y = (x + 5)^2 + 49 \][/tex]

First, we will expand the [tex]\((x + 5)^2\)[/tex] term using the distributive property or the formula for squaring a binomial [tex]\((a + b)^2 = a^2 + 2ab + b^2\)[/tex].

[tex]\[ (x + 5)^2 = x^2 + 2 \cdot x \cdot 5 + 5^2 \][/tex]
[tex]\[ (x + 5)^2 = x^2 + 10x + 25 \][/tex]

Now, substitute this expanded form back into the original equation:

[tex]\[ y = (x + 5)^2 + 49 \][/tex]
[tex]\[ y = x^2 + 10x + 25 + 49 \][/tex]

Next, combine the constant terms (25 and 49):

[tex]\[ 25 + 49 = 74 \][/tex]

So the equation in standard form is:

[tex]\[ y = x^2 + 10x + 74 \][/tex]

Therefore, the standard form of the equation is:
[tex]\[ y = x^2 + 10x + 74 \][/tex]

The correct answer is:
C. [tex]\( y = x^2 + 10x + 74 \)[/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.